Investigation of Relationship between Level of Awareness around Health, Safety and Environment Management System and Its Effects on Safety Climate and Risk Perception by Employees in an Iran Oil Refinery, 2015 - Milad Ahmadi Marzaleh; Shahram Vosoughi; Amir Kavousi; Hosein Jameh Bozorg (Iranian Journal of Health, Safety and Environment, 2017)
Special attention of and oil, gas and petrochemical large corporation in the world to the HSE management system is due to its importance in the designing and development of products, services and processes by considering its health, safety and environment requirements. Staff's perception of the existing job risks has a significant impact on their safe behavior at work. This study was conducted to determine the relationship between safety climate and staff's perception of risk with an awareness level among employees of the HSE management system in an oil refinery in Kermanshah. The study population was employees in one of the oil refineries in Iran. After designing and questionnaire psychometric assessment of staff knowledge of HSE management system (Cronbach's alpha was 0.9 and its validity was assessed by certified professionals), Loughborough safety climate questionnaire and Flin risk perception questionnaire were used. Data analysis was performed using SPSS V22 software. Results showed that the relationship between safety climate and awareness level of the HSE management system; also the relationship between safety climate and perception of risk was also getting significant. However, the relationship between perception of risk and awareness level of the HSE management system was not significant. The results of this study showed a moderate awareness of HSE Management System in refinery workers. In this regard, appropriate and proper management policy should be committed to improving the situation. The results of this study is a profile the situation of safety climate in the refinery, which can be used as an indicator for the development of preventive policies and evaluate the performance of the organization's safety and the results of the safety improvement organization.